Development and Evaluation of Controlled Release Bilayer Tablets of Hydrochlorothiazide and Losartan Potassium - Manoj Kumar Mishra; Dubey Deepti; Upamanyu Neeraj (Journal of Pharmacy and Nutrition Sciences, 2015)
The aim of the present research work was to develop bilayer tablet dosage form containing combination of immediate and sustained matrix prepared from Hydrochlorothiazide (HTZ) and Losartan Potassium (LP) respectively for the treatment of hypertension and its associated complications. Immediate release HTZ was prepared using different superdisintegrants. LP sustained layer was prepared by compression technique. Both pre-compression and post-compression parameters were analyzed for all the tablets. In vitro release studies were carried out as per USP in pH (1.2) and phosphate buffer pH (6.8) using USP-XXI type II. Bilayer tablet (F6) formulated using higher concentration of HPMC K 15 exhibiting higher LP release rate (83.553± 0.22) for the period of 12 h. The In vitrorelease profile of drug from sustained matrix could be best expressed by First order as the plot showed highest linearity (R2 = 0.990) and diffusion was the dominating mechanism of drug release. The stability and FTIR studies are also indicating the absence of strong interaction between drug and polymer and compatibility among them.